ASSESSING FINANCIAL PERFORMANCE AND COMPANY VALUATION WITHIN THE FRAMEWORK OF PT XYZ'S LONG-TERM PLAN - Syafiq Ziyad; Oktofa Yudha Sudrajad (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study evaluates the financial performance and determines the fair value of PT XYZ, a state-owned Indonesian coal mining company, within the framework of its Long-Term Corporate Plan (RJPP). In an era of fluctuating coal prices and increasing pressure for energy transition, mining companies face challenges in maintaining profitability while planning for future sustainability. The research aims to assess PT XYZ's financial health from 2021-2023 based on the Decree of the Minister of SOEs No. KEP-100/MBU/2002 and determine its fair value using established valuation methodologies. Using a mixed-method approach, the study analyzes secondary data from financial statements, coal price forecasts, and strategic planning documents. Findings reveal that PT XYZ improved from an AA rating in 2021-2022 to AAA in 2023, despite challenges in inventory management due to transportation constraints. The FCFF valuation across three scenarios, optimistic, moderate, and pessimistic, yielded enterprise values ranging from IDR 27.7-84.4 trillion, with the moderate scenario providing the most realistic assessment at IDR 33 trillion. Relative valuation using PER and PBV metrics further suggests potential undervaluation in moderate and optimistic scenarios. The research concludes that PT XYZ's financial health and valuation are significantly dependent on infrastructure development timelines and the successful implementation of diversification strategies aimed at mitigating long-term coal demand decline. Strategic recommendations emphasize adherence to project execution timelines, alignment of financing strategies, and acceleration of diversification initiatives to maximize long-term value.